Assessment of depression and anxiety in patients with chronic liver disease - Popović, Dušan Dj.; Ćulafić, Djordje M.; Kisić Tepavčević, Darija B.; Kovačević, Nada V.; Špuran, Milan M.; Djuranović, Srdjan P.; Jovičić, Ivana A.; Krstić, Miodrag N.; Perišić, Mirjana D.; Pekmezović, Tatjana D. (Vojnosanitetski pregled, 2015)
Background/Aim. In recent years mental health of patients including those with chronic liver disease (CLD), has become interesting because its disturbance leads to reduced quality of life, that is associated with worsening of clinical outcome, reduced compliance and increased mortality. The aim of the study was to determinate the frequency and severity of depression and frequency of anxiety in patients with CLD and to assess the contribution of selected socio-demographic, clinical and laboratory risk factors for depression and anxiety. Methods. In this cross-sectional study, we used the Hamilton depression rating scale (HDRS) and Hamilton anxiety rating scale (HARS) in patients with CLD. Results. The study included 54 male and 43 female patients. Depression was present in 62.9%, and anxiety in 13.4% of the patients. A higher HDRS was noted in the patients older than 50 years (p = 0.022) and unemployed patients (p = 0.043). The patients with at least one episode of gastrointestinal bleeding had a significantly higher frequency of anxiety than those without bleeding (p = 0.018). A higher HARS score was present in the women (p = 0.011), unemployed patients (p = 0.008) and those with non-alcoholic liver disease (p = 0.007). There was a significant correlation between the mean corpuscular volume (MCV) and the value of the HDRS score, and between serum potassium and sodium levels and HDRS score. Conclusion. Age and the mean corpuscular volume have significant influence on the HDRS score while unemployment, gastrointestinal bleeding, serum potassium and serum sodium have predictive value for HARS score.